Evaluation of Wound Healing Activity of Angiotensin Converting Enzyme Inhibitors in Wistar Rats - Majagi*, V.V. Gouripur, P.A. Patil, A.P. Hogade, S.S. Torgal, S.V. Hiremath, Suneel I. (Recent Research in Science and Technology, 2010)
Angiotensin converting enzyme (ACE) inhibitors are known to increase the level of bradykinin by preventing its breakdown and also promote prostaglandin synthesis by direct and indirect methods which in turn may promote wound healing. However there is paucity of scientific information in this regard. Therefore in the present study we have investigated the effect of ACE inhibitors like Captopril and Enalapril on different wound models in Wistar rats. Excision, resutured incision and dead space wounds were inflicted in male Wistar rats under light ether anaesthesia, taking aseptic precautions. Control animals received vehicle and other groups received Captopril (10mg/kg) and Enalapril (10mg/kg) orally for a period of 10 days in incision and dead space wound models, whereas similar treatments were continued in excision wound models till complete closure of wounds. On the 11th day, after estimating breaking strength of resutured incision wounds (under anaesthesia), granulation tissue was removed from dead space wounds to estimate breaking strength, hydroxyproline content as well as quantification of granulation tissue and histological studies were carried out in control and treated groups. Captopril and Enalapril significantly increased the rate of wound healing, reduced the number of days required for complete epithelialization and final area of scar in excision wounds. Both the ACE inhibitors significantly increased breaking strength of resutured incision wounds and granulation tissue. Also these two drugs significantly enhanced both granulation tissue formation and granulation tissue hydroxyproline content. Histological studies confirmed these findings. Captopril and Enalapril significantly promoted the healing process in all the three wound models studied. These results indicate the wound healing property of ACE inhibitors and clinical studies in this regard are worthwhile.